Backward Versus Forward Integration of Firms in Global Value Chains - Peter H. Egger; Katharina Erhardt; Gerard Masllorens (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Production processes are increasingly organized in international value-chain networks. The involved firms can be operating at arm's length or be vertically integrated. Both the incidence and the direction of integration (backward or forward in the value chain) depend on specific characteristics of the firms and their economic environment. We propose a simple model of vertical integration in a supplier-producer relationship that is rooted in the property-rights theory to learn about the determinants of forward versus backward integrations. Generally, the profitability and direction of integration depend on the relative investment intensity of the producer and the supplier so as to align investment incentives and maximize joint surplus. Moreover, the organizational form depends on the fixed costs of firm integration and the market environment in the input market as well as the relative importance of the specific input for the final output. These results are strongly confirmed in a large panel of worldwide directed ownership linkages.
Keywords: L14; L22; L23; L24; 330; firm integration; global value chains; investment